What’s up Your Grace : An Analysis of Informal Language and Modern Slang in Historical Films - Kuutti, Maija (My University, 2026)
Informal language and modern slang are considered non-standard language varieties in the context of historical cinema, in which formal register is preferred. Hence, the effects of using informal language and slang in historically set films are still relatively unknown. The aim of this thesis is to analyse the functions of these unconventional language varieties in two historical films. Additionally, this study aims to recognise how informal language and modern slang influence the speaker’s character identity. The data is collected from two films of differing genres, the romance film Persuasion and the parody film Robin Hood: Men in Tights, to construct a more comprehensive study. The data examined consists of contractions, slang terms, anachronistic expressions and informal discourse markers. These indicators of informal register and modern slang are analysed through Multi-Dimensional Analysis and pragmatics. The results of this study indicate that incorporating informal language and modern slang into historical films’ dialogues can, for instance, create humour and relatability by using contemporary language in unexpected ways. Furthermore, this study contributes to broader discussions on how unexpected linguistic choices can affect narratives, characterisation and audience engagement in historical cinema.
Keywords: informal register; formal register; slang; historical films; Multi-Dimensional Analysis; pragmatics